Effects of urocortin on spine? - Sehmisch, S.; Komrakova, M.; Kottwitz, L.; Dullin, C.; Schmelz, U.; Stuermer, K. M.; Tezval, M. (Osteologie, 2015)
Urocortin (UCN) is a member of the cortico tropin-releasing factor family. UCN enhances osteoblast differentiation and inhibits osteoclasts in vitro. In the present study, the effect of UCN on spine was assessed in the rat osteopenia model.Sprague Dawley rats (3 month old) were either ovariectomized (OVX, n = 48) or sham operated (n = 12). After 9 weeks, OVX rats were divided into 4 groups (n = 12): OVX, UCN low (3 µ/kg BW), UCN high (30 µ/kg BW), estradiol-17β-benzoate (0.2 mg/kg BW). UCN was administered daily s. c., estrogen was supplied with food for 35 d. Thereafter, the lumbar vertebral bodies were analyzed by biomechanical test, micro-CT, pQCT, gene expression and ashing analyses. Serum alkaline phosphatase (AP), beta-Crosslaps, calcium, leptin levels were assessed.Stiffness, BMD, BV/TV, trabecular parameters improved in UCN high group. UCN low dose had less effect on spine. AP was enhanced in UCN high group, leptin increased in both UCN groups, other serum parameters and expression of bone genes did not change. UCN high dose showed osteoprotective effect in spine.Further studies are needed to understand mechanism of UCN action on bone and to reveal potential side effects.
Keywords: Urocortin; lumbar spine; ovariectomized rat; biomechanics